1999
DOI: 10.1021/jp990654y
|View full text |Cite
|
Sign up to set email alerts
|

A Hidden Hydrogen Transfer in the Unimolecular Reaction of 1,2-Dimethoxyethane•+

Abstract: The metastable dimethoxyethane radical cation 1 eliminates methanal to give the CH3O+(H)CH2C•H2 distonic ion 2 (m/z 60, 80%) and methanol to yield the C3H6O•+ (m/z 58, 20%) fragment. The first process is well-known, beginning with the transfer of a hydrogen from a methoxy group to the oxygen of the other to yield the intermediate distonic ion •CH2OCH2CH2O+(H)CH3, 3. It is shown, from FTICR experiments, that the m/z 58 fragment possesses the CH3OCHCH2 •+ structure 5. From energetic studies, it can be establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…This implies that the highly excited states of the glyme primary RCs are unlikely involved in the reactions, which is apparently facile even in the ground state of the RCs. The shapes of the TR MFE curve are nearly the same in a wide temperature range, which indicates that in the liquid state (as opposed to the gas phase experiments 12 ) the conversion of the primary RCs of glymes to the secondary RCs has negligible energy barriers.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…This implies that the highly excited states of the glyme primary RCs are unlikely involved in the reactions, which is apparently facile even in the ground state of the RCs. The shapes of the TR MFE curve are nearly the same in a wide temperature range, which indicates that in the liquid state (as opposed to the gas phase experiments 12 ) the conversion of the primary RCs of glymes to the secondary RCs has negligible energy barriers.…”
Section: Resultsmentioning
confidence: 79%
“…A study of the monoglyme RC decomposition in the gas phase suggested that the most favorable reaction for the isolated RC was the methyl alcohol elimination yielding the methyl vinyl ether RC, CH 3 –O–CHCH 2 •+ . The postulated decay includes three sequential intramolecular H atom transfers, a, b, and c (the maximum barrier is about 10 kcal/mol), followed by the C–O bond cleavage as shown in Scheme .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ionized dimethyl ether of ethylene glycol, CH 3 OCH 2 CH 2 OCH 3 , would be another closely related system, but hydrogen atom abstraction initiates the prominent reactions of the metastable molecular ions also in this case; rearrangement precedes fragmentation. 15,16 However, Tobita's report 15 includes a low-resolution MIKE spectrum of a labeled analog, which demonstrates that the low-yield simple cleavage of the CC bond is accompanied by an α-secondary isotope effect similar to that described here for TMEDA.…”
Section: Scheme 4 Simple CC Cleavage Is Not a Prominent Reaction Of mentioning
confidence: 75%
“…The peak at m/z 90 originates from the photoionization of the dimethoxyethane (C4H10O2, MW 90.12) solvent molecule, and m/z 45, 58, and 60, are from dissociative photoionization of the dimethoxyethane ion. 17 The peak at m/z 74 is from the photoionization of dioxolane (C3H6O2, MW 74.08), and m/z 73 (C3H5O2 + ) is from dissociative photoionization as observed in previous electron impact studies. 18 The application of a potential to the SALVI E-cell does not affect the intensity of solvent peaks.…”
mentioning
confidence: 65%